Application of the TAM Model and Financial Literacy on Interest in QRIS Digital Payments (Study on Semarang State Polytechnic Students) - Wijayanto, Edi; Yeni Martia, Dina; Adhi, Nurseto; Rikawati, Rikawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
With the rapid development of digital technology, especially in the payment field, digital payment services using QR codes are becoming more popular. The Quick Response Code Indonesia Standard (QRIS), introduced by Bank Indonesia and the Association of Indonesian Payment Systems (ASPI) on August 17, 2019, will serve as the national QR code standard and facilitate payments across Indonesia. QRIS allows you to apply for payments to a variety of institutions, bank or non-bank. This study involved 370 of his students from a population of 6,128, used structural equation modeling (SEM) for analysis, and showed a robust fit with his GFI value above 0,917. The results show that the TAM variables (perceived ease of use, usefulness, enjoyment, and financial literacy) significantly influence his interest in implementing QRIS, which increases his 5% is supported by a probability value less than or equal to.